Examination of associations between risky driving behaviors and hazardous drinking among a sample of college students. (18th August 2018) - Martin, Ryan J.; Cox, Melissa J.; Chaney, Beth H.; Knowlden, Adam P.
Abstract: Objective: Hazardous drinking is associated with other risky behaviors and negative health-related outcomes. This study examined covariation between hazardous drinking scores and the following risky driving behaviors: Falling asleep while driving, texting (receiving and sending) while driving, and driving after consuming alcohol. Methods: The participants in this study were a sample of undergraduate students ( N = 1, 298) who were enrolled in an introductory health course at a large Southeastern university in spring 2016 and completed an online health survey that assessed hazardous drinking, falling asleep while driving, texting while driving, and driving after consuming alcohol. We conducted a series of 2-step regression analyses to examine covariation between hazardous drinking scores (using the Alcohol Use Disorders Identification Test–Consumption [AUDIT-C]) and the risky driving behaviors of interest. Results: We found that the majority of participants did not drink and drive (91.8%), nor did they fall asleep while driving (80.4%); however, the majority did read a text while driving (81.7%) and sent a text while driving (75.3%). In the full multivariable model, hazardous drinking score was positively associated with drinking and driving (step 2 odds ratio [OR] = 1.28, 95% confidence interval [CI], 1.18, 1.38) and sending a text message while driving (step 2 b = 0.19, P = .01). Hazardous drinking score was also positively associated with reading a text while driving (step 1 b = 0.14, P < .001) and falling asleep while driving (step 1 b = 0.02, P = .02) in the model only controlling for demographic characteristics. The analyses also indicated covariability between the following risky driving behaviors: (1) drinking and driving/reading a text message while driving, (2) drinking and driving/falling asleep and driving, (3) reading a text while driving/sending a text while driving, and (4) sending a text while driving/sleeping and driving. Conclusion: The findings of this study indicate a need for interventions discouraging both hazardous drinking and risky driving behaviors in college student populations; recommendations to reduce risky driving and hazardous drinking are discussed.